PERUBAHAN TUTUPAN LAHAN DI DAS WAERUHU KOTA AMBON MENGGUNAKAN CITRA SATELIT MULTITEMPORAL - Yulien A. Tayane; Aryanto Boreel; Jusmy D. Putuhena (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2021)
This study aims to determine landcover changes in the Wae Ruhu watershed for a period of 15 years (2004-2019) and identify factors that influence landcover changes in the Wae Ruhu watershed Sirimau District, Ambon City. The data used in this study are Landsat 7 ETM+ C1 Level-1 Imagery in 2004 and Landsat 8 Path 109 Row 62 OLI/TIRS CI Image Level-1 in 2019 which were downloaded from www.earthexplorer.usgs.gov. The stages of satellite image processing carried out include: pre-processing, processing and post-image processing. Land cover classification was carried out using a guided classification. The results showed that the trend of land cover changes in the Wae Ruhu watershed, Ambon City over a period of 15 years, was very dynamic. The area of ​​primary dry land forest cover in 2019 decreased by 524,21 ha from 2004, while the area of ​​secondary dry forest cover increased by 764,42 ha followed by 195,26 ha. The phenomenon of land cover changes in the Waeruhu watershed of Ambon city is thought to be caused by an increase in population, ease of access such as the availability of road and river networks, and the emergence of infrastructure.